17α-ethinylestradiol breakthrough in soil - Oliveira, Renan Angrizani de; Tardelli, Edgard Robles; Jozala, Angela Faustino; Grotto, Denise (Revista Hipótese, 2019)
17α-ethinylestradiol (EE2) is a synthetic hormone widely used with hard degradation. Through the breakthrough, is observed the transport in the soil, collected from a region with vegetal cover to study the behavior of EE2 in fixed bed. The final concentrations of EE2 obtained in the experiments were quantified by high performance liquid chromatography. Thus, the breakthrough obtained for EE2 in the soils was defined in 40 min in the study.
Keywords: Endocrine disrupters; Adsorption; Contamination; Fixed Bed